Stakeholder Collaboration in The Management Of Star Fruit Agro-Tourism (Case Study In Watesari Village, Balongbendo Sub-District, Sidoarjo District): Kolaborasi Stakeholder Dalam Pengelolaan Agrowisata Belimbing (Studi Kasus di desa Watesari Kecamatan Balongbendo Kabupaten Sidoarjo) - Muwardi, Alifiah Arum; Kusumawati, Elena Febri; Muslimah, Mei Syaroh (Universitas Muhammadiyah Sidoarjo, 2022)
Stakeholder collaboration that goes well is the main key to realizing a goal. In the management of a tour requires good collaboration from the parties who participate in managing the tour. Collaboration carried out by stakeholder actors must be coordinated intensively so that the goals in an organization can be realized. Tourism is one part of the industrial sector that has the potential and opportunity to be developed. Tourism is an industrial sector that is interrelated with other sectors, one of which is the Micro, Small and Medium Unit sector. The method of community service activities was adapted from Vincent II (2009. The purpose of establishing this starfruit agrotourism is to open up job opportunities for the residents of Watesari Village and be able to provide village creations that can be developed and marketed abroad. Watesari agro-tourism, Watesari village-owned enterprise and starfruit garden managers. All these stakeholders have their respective roles in the management of star fruit agro-tourism.